Do the Welsh have it? Evaluating a bereavement support service supporting people bereaved by dementia. Issue 2 (2nd September 2019) - Roleston, Caity; West, Karen; Shaw, Rachel
Abstract: Accumulating evidence suggests that a dementia diagnosis, for many, triggers feelings of grief, and often marks the first of many losses that will be experienced by both the person who has received the diagnosis and their loved ones, as the disease progresses. Previous research has also revealed that carers who report higher levels of pre-death grief are at greater risk of complicated grief after their loved one has died. Despite this evidence, appropriate bereavement support for people bereaved by dementia is a significant unmet need. The Bereaved by Dementia project was delivered collaboratively by Cruse Cymru and Alzheimer's Cymru to address the bereavement needs of people bereaved by dementia throughout Wales. This paper draws on an independent evaluation of the Bereaved by Dementia Project conducted by Aston University and the University of Bristol. We summarise our main findings, recommendations, and suggestions for future research.